1968
DOI: 10.1128/jvi.2.10.1047-1054.1968
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and Autoradiographic Studies of Cells Infected with Herpes Simplex Virus

Abstract: The induction of chromosomal aberrations by herpes simplex virus (HSV) and the interaction between viral deoxyribonucleic acid (DNA) and chromosomes have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The described association with condensed chromatin or chromosomes were chance observations, because the parental DNA was localized just as frequently in the nucleoplasm without any particular association with condensed chromatin material. These results confirm published observations by light microscopy in which it was found that most of the viral DNA remains unassociated with chromosomes and is not detectable at sites of chromosomal lesions (12).…”
Section: Discussionsupporting
confidence: 92%
“…The described association with condensed chromatin or chromosomes were chance observations, because the parental DNA was localized just as frequently in the nucleoplasm without any particular association with condensed chromatin material. These results confirm published observations by light microscopy in which it was found that most of the viral DNA remains unassociated with chromosomes and is not detectable at sites of chromosomal lesions (12).…”
Section: Discussionsupporting
confidence: 92%
“…In vitro, a variety of herpes simplex virus (HSV)-induced effects on the host cell genome have been described. HSV has been shown to induce chromosomal aberrations (8,22,62) and host cell DNA repair (43). HSV induces point mutations within the host cell genome, with an efficiency similar to that of chemical carcinogens (49,50,59).…”
mentioning
confidence: 99%
“…Our findings are also in agreement with those of studies in which breakage has been investigated in cells infected in vitro with herpes sitnplex viruses. Increased breakage and other aberrations have been found in Chinese hamster cells (11,12), in monkey kidney cells (13), in human cell lines HeLa and Hep-2 (14), in human embryo kidney cells (15), in human leukocytes (16,17), and in human diploid fibroblasts (18); also, in human embryo lung cells (15,19) and in human embryo kidney cells and leukocytes (15) after infection with herpes simplex virus Type 2 (HSV-2). On the contrary, in a few studies no damage has been found in human embryo lung cells and in phytohaemagglutinin-stimulated peripheral blood leukocytes aftter infection with HSV-1 (15).…”
Section: Discussionmentioning
confidence: 99%